Implementasi Pendidikan Karakter dalam Pembelajaran Matematika dengan Menggunakan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization - Lintal Muna; Yani Djawa (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
In the era of globalization we need the implementation of character education for self-limiting, given that in the era of globalization, it is difficult to recognize cultural boundaries. Therefore, it takes an integrated character education on the subjects, thus indirectly the character education has been applied. To implement an integrated character education in the subjects, required learning model that suits the character that will be applied. Team assisted individualization is one type of cooperative learning model in a way students work in cooperative learning groups and is responsible for setting and checking on a regular basis, helping each other solve problems and to encourage each other to excel. The purpose of this study is not to implement character education in mathematics using cooperative learning model Team Assisted Individualization (TAI) and know the results of students of class V SD Negeri 3 Weda. This study is a class action (Classroom Action Research) collaborative and in the form of a cycle. The subject of research is a class V SD Negeri 3 Vedas. The instrument used was a test, observation sheets, interview, and documentation. The results showed that an increase in the learning outcomes of pre-cycle where students learning completeness 0% increase in the first cycle to the second cycle of 40% and 76%. The same thing can be seen in the ability of teachers to manage the classroom, in the first cycle teachers value increased in the second cycle of 3.75 to 4.58 with both categories. For the implementation of the integrated character education in mathematics can be seen in the first cycle of 98.67% the percentage of character discipline, teamwork 96%, and the responsibilities of 86.71%. In the second cycle, 98.76% of students have had the character of discipline, 96.90% students have the character of cooperation, and 88.89% of students have had the character of responsibility.